SIGNIFICANCE OF STIMULATING GROWTH FACTOR ST2 AND NT-proBNP IN ASSESSMENT OF POSTINFARCTION REMODELING OF THE HEART - Yu. A. Dyleva; O. V. Gruzdeva; O. E. Akbasheva; E. G. Uchasova; N. V. Fedorova; A. G. Chernobay; V. N. Karetnikova; S. N. Kosareva; V. V. Kashtalap; T. S. Fedorova; O. L. Barbarash (Российский кардиологический журнал, 2015)
Aim. To assess the levels of ST2 and NT-proBNP in serum of infarction patients (MI) in dynamics of hospital period and their relation with adaptive and desadaptive variants of myocardium remodeling.Material and methods. Totally, 87 patients (65 men and 22 women) with MI with ST elevation (STEMI), of those 67 patients had adaptive, physiological variant, and 20 — desadaptive, pathological variant of myocardium remodeling (DR). Mean age of patients was 59±8,36 y. In control group entered 30 patients. At 1st and 12th day of MI we studied in blood serum via immune enzyme method the levels of ST2 and NT-proBNP with test-systems of Critical Diagnostics (USA) company and Biomedica (Slovak Resp.), respectively. Statistical analysis of the data was performed with non-parametric criteria.Results. On the 1st day of hospitalization period of MI concentration of ST2 and NTproBNP increased comparing with controls, 2,4 times and 4,5 times, respectively. In DR the level of ST2 on the 1st day was 1,5 times higher, than in the group of adaptive remodeling and 5,3 times higher comparing with the group of control. On the 12th day, in both groups there was decrease of marker level. Concentration of NT-proBNP did not relate on the type of post infarction remodeling and on the 1st day it was increased among the patients of both groups 1,8 times comparing with controls. High level of ST2 on the 1st day of MI increases the risk of DR 4,5 times (OR=4,5, 95% CI=2,0-10,1, р=0,011, AUG was 0,81, sensitivity — 78,7%, specificity — 69,4%), though the increase of NT-proBNP — just 2,3 times (OR=2,3, 95% CI=2,0-2,01, р=0,032, AUG was 0,68, sensitivity — 69,5%, specificity — 65,9%).Conclusion. So, in MI in 23% cases there was DR variant. High level of ST2 stimulating factor on the 1st day of MI is associated with the development of this type of remodeling and makes to predict the risk with higher sensitivity and specificity comparing with NTproBNP.